2020
DOI: 10.1101/2020.12.04.411793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recognition of Z-RNA by ADAR1 limits interferon responses

Abstract: Nucleic acids are powerful triggers of innate immunity and can adopt the unusual Z-conformation. The p150 isoform of adenosine deaminase acting on RNA 1 (ADAR1) prevents aberrant interferon (IFN) induction and contains a Z-nucleic acid binding (Zα) domain. We report that knock-in mice bearing two point mutations in the Zα domain of ADAR1, which abolish binding to Z-form nucleic acids, spontaneously induced type I IFNs and IFN-stimulated genes (ISGs) in multiple organs. This included the lung where both stromal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Subsequent experiments demonstrated that the mouse equivalent to the P193A variant recapitulated the human Zα mendelian phenotype [36]. Three other recently generated mouse models using different loss of function Zα residues variants also were associated with a type I interferon signature [37][38][39]. Taken together, the data confirmed the biological relevance of the Z-conformation and provided evidence for its role in the regulation of type I interferon responses.…”
Section: Adar1 and Human Diseasementioning
confidence: 70%
See 1 more Smart Citation
“…Subsequent experiments demonstrated that the mouse equivalent to the P193A variant recapitulated the human Zα mendelian phenotype [36]. Three other recently generated mouse models using different loss of function Zα residues variants also were associated with a type I interferon signature [37][38][39]. Taken together, the data confirmed the biological relevance of the Z-conformation and provided evidence for its role in the regulation of type I interferon responses.…”
Section: Adar1 and Human Diseasementioning
confidence: 70%
“…A common finding was that there was extensive overlap in the edits made by each isoform, with p150 edits occurring mostly in Alu elements, with around 50% occurring in 3 0 untranslated regions (UTRs) in mice [44,45]. The further analysis of p150 biology in mice with Zα loss of function variants was confounded by the presence of p110 that edits many substrates in common with p150 as expected from their shared dsRNA and deaminase domains [37][38][39]46]. In a technical tour de force, Kim and colleagues succeeded in creating a mouse that expressed only p150, but with no detectable p110 [47].…”
Section: The Importance Of Adar1 P150mentioning
confidence: 99%
“…In particular, when other cell death pathways are inactivated by mutation, necroptosis that is dependent on ZBP1 produces inflammation and disease due to necroptosis. Other labs (Jon Maelfait [ 21 ], Jan Rehwinkel [ 22 ] and Andrew Oberst (unpublished) presented studies from mouse models to examine the genetic interactions between ZBP1, MDA5 and ADAR1 and their outcomes, in particular on live births. Preliminary results were presented showing that in certain crosses, embryonic lethality was associated with high interferon responses in the mother but not dependent on the paternal genotype.…”
Section: Meeting Summarymentioning
confidence: 99%
“…However, the detail of the protective mechanism against cell death remains to be explored. Recently, several individual studies revealed that RNA deaminase ADAR1 edits endogenous Z-form RNA [44][45][46], suggesting ADAR1 might be a negative regulator by degradation the ligand of ZBP1.…”
Section: Negative Regulation Of Zbp1-dependent Cell Deathmentioning
confidence: 99%